WHICH BRAZILIAN CAPITAL PROMOTE GREATER SOCIAL WELL-BEING? (Gestão & Regionalidade, 2025)
Observing the heterogeneities of Brazilian state capitals and access to social welfare policies (health, education, assistance and social security), this study seeks to assess and classify income equality, development and access to social policies, in addition to the correlation between such aspects in national capitals. Theoretically, it addresses the Welfare State, public policies, development and inequality. This is a quantitative study that uses bibliographic, descriptive, geostatistical and Pearson correlation coefficients. The results show that there are few capitals that can be cited as promoters of social well-being, pointing out Florianópolis and Curitiba. Finally, the associations between development and welfare and social assistance policies and income deconcentration and access to public education are highlighted.